Development of Yellow Discoloration in Sawai (Pangasianodon hypophthalmus) Muscle due to Lipid Oxidation - Chodsana Sriket; Phanat Kittiphattanabawon; Umesh Patil; Soottawat Benjakul; Theeraphol Senphan; Sitthipong Nalinanon (My University, 2023)
In this study, we investigated the impact of lipid oxidation on the discoloration of Sawai (
Keywords: Lipid Oxidation; Thiobarbituric acid; Browning; Myofibril; Meat and Animal Product Quality